Urinary antigen testing in community-acquired pneumonia in adults: an update. Issue 2 (1st February 2019) - Viasus, Diego; Calatayud, Laura; McBrown, María V.; Ardanuy, Carmen; Carratalà, Jordi
ABSTRACT: Introduction : Community-acquired pneumonia (CAP) continues to be a leading cause of hospitalization and mortality worldwide. Streptococcus pneumoniae and Legionella pneumophila remain the major etiological agents and are responsible for a significant proportion of CAP mortality. Among diagnostic tests for CAP, urine antigen detection of S. pneumoniae and L. pneumophila is widely accepted due to the simplicity of collection and the rapidity of the test results. Areas covered : This comprehensive review outlines the urinary antigen tests available, discusses their sensitivity and specificity, and assesses the usefulness of their results as the basis for targeted therapy. Expert commentary : There have been advances in urine antigen detection tests for patients with CAP. New methodologies show greater sensitivity, detect S. pneumoniae and L. pneumophila in a single test, and also detect pneumococcal serotypes. In addition, urine antigen detection tests have shown a high specificity, which means that a positive result practically indicates the causative pathogen of CAP. Therefore, a positive result can lead to a targeted therapy that is likely to improve patient outcomes and reduce the risk of resistance and adverse events. However, well-designed studies are needed to evaluate the usefulness of urine antigen detection tests with regard to clinical outcomes.